2012
DOI: 10.1152/ajpendo.00057.2011
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term leptin exposure differentially affect human natural killer cell immune functions

Abstract: Epidemiological studies have indicated that obesity is associated with a higher risk for certain cancers caused by elevated levels of adipocyte-derived hormones. Leptin, one such hormone produced by adipocytes, is a major regulator of metabolism and has also been shown to modulate immunity. However, its role in regulating human natural killer (NK) cell functions is largely unknown. Here, we show that the leptin receptor (Ob-R) is expressed on 5% of NK cells isolated from blood donors, as measured with flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
83
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 61 publications
(74 reference statements)
9
83
1
5
Order By: Relevance
“…Interestingly, a study with a large cohort demonstrated that plasma leptin levels are stronger linked to a cardiovascular death in males than in females [26]. Furthermore, it could be shown that high-elevated leptin levels in obese individuals result in the development of a leptin resistance [10]. The data from this study demonstrate for the first time that numbers of peripheral CTLs and NK cells are decreased in pre-operative obese patients when compared to normal weight patients suffering from osteoarthritis.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Interestingly, a study with a large cohort demonstrated that plasma leptin levels are stronger linked to a cardiovascular death in males than in females [26]. Furthermore, it could be shown that high-elevated leptin levels in obese individuals result in the development of a leptin resistance [10]. The data from this study demonstrate for the first time that numbers of peripheral CTLs and NK cells are decreased in pre-operative obese patients when compared to normal weight patients suffering from osteoarthritis.…”
Section: Discussionmentioning
confidence: 61%
“…In prior studies, it was demonstrated that long-term effects of the adipokine leptin led to immunomodulatory functions on various immune cells including NK cells [10]. Due to the fact that leptin expression correlates with the amount of adipose tissue [24], the immunomodulatory effects of long-term leptin incubation on immune effector cells could be an explanation for the reduced wound healing in overweight and obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the role of adipocytes on malignance has been suggested via tumor-stroma interaction required during metastases or early micrometastases [13]. Recent data also suggest that adipocytes not only respond to hormonal signals, but also produce hormone-like factors such as pro-inflammatory leptin that may enhance oncological risk [14]. Although it is not clear how leptin interacts in IGF-1 mitogenic signaling, our previous studies conducted in TPA-promoted mouse skin cancer model have demonstrated that the reduction of both IGF-1 and leptin levels in response to weight loss corresponded to a concomitant inhibition of IGF-1-dependent mitogenic cascades and thus diminution of TPA-promoted signaling [5,6,15].…”
mentioning
confidence: 99%